2017
DOI: 10.3310/hta21080
|View full text |Cite
|
Sign up to set email alerts
|

CollAborative care and active surveillance for Screen-Positive EldeRs with subthreshold depression (CASPER): a multicentred randomised controlled trial of clinical effectiveness and cost-effectiveness

Abstract: BackgroundEfforts to reduce the burden of illness and personal suffering associated with depression in older adults have focused on those with more severe depressive syndromes. Less attention has been paid to those with mild disorders/subthreshold depression, but these patients also suffer significant impairments in their quality of life and level of functioning. There is currently no clear evidence-based guidance regarding treatment for this patient group.ObjectivesTo establish the clinical effectiveness and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…50 The effect size is consistent with findings from systematic reviews of collaborative care, as summarised in a recent Cochrane review, 22 and is also of the same order of magnitude as that seen in UK trials of collaborative care for working-age adults, such as those observed in the recently published CADET 69 and also in the recently completed CASPER trial for older people with lower-severity depression. 29,30 The CASPER plus trial also showed benefits across a range of secondary outcomes, and it was notable that there were improvements in anxiety symptoms, somatoform symptoms and quality of life (mental domain as measured by the SF-12). These benefits were seen in the short term (4 months) and were also sustained at 12 months for secondary outcomes (but not for the outcome of depression severity).…”
Section: Discussion Of Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…50 The effect size is consistent with findings from systematic reviews of collaborative care, as summarised in a recent Cochrane review, 22 and is also of the same order of magnitude as that seen in UK trials of collaborative care for working-age adults, such as those observed in the recently published CADET 69 and also in the recently completed CASPER trial for older people with lower-severity depression. 29,30 The CASPER plus trial also showed benefits across a range of secondary outcomes, and it was notable that there were improvements in anxiety symptoms, somatoform symptoms and quality of life (mental domain as measured by the SF-12). These benefits were seen in the short term (4 months) and were also sustained at 12 months for secondary outcomes (but not for the outcome of depression severity).…”
Section: Discussion Of Main Findingsmentioning
confidence: 99%
“…To detect a minimum standard effect size of 0.35 (aligning with the US IMPACT study 16 and our previous CASPER trial 29,30 ) with 80% power and a two-sided 5% significance level, 260 patients (130 per arm) would be required. Although this is an individually randomised trial, there may be potential clustering at the level of each collaborative care case manager, and hence the sample size was inflated to account for this.…”
Section: Sample Sizementioning
confidence: 99%
“…Seven studies (Buntrock et al 2017;Fernandez et al 2018;Ophuis et al 2018;Ride et al 2016;Uegaki et al 2011;van den Berg et al 2011;van Oostrom et al 2010) evaluated interventions delivered to the general population, mainly adults over 18 years old. Four interventions were delivered at primary and maternity care centers (Fernandez et al 2018;Ophuis et al 2018;Ride et al 2016;van den Berg et al 2011), two were delivered in the workplace (Uegaki et al 2011; van Oostrom et al (Coulton et al 2015;Lewis et al 2017). Six studies (Anderson et al 2014;Lee et al 2017;Lynch et al 2005;Mihalopoulos et al 2012;Philipsson et al 2013;Stallard et al 2015) evaluated seven interventions targeting children and adolescents under 18 years.…”
Section: Population Age Groups Type Of Intervention and Arenamentioning
confidence: 99%
“…Four studies (Anderson et al 2014;Buntrock et al 2017;Lewis et al 2017;van Oostrom et al 2010) aimed to promote mental health were considered to be of high quality, but none of the studies that evaluated suicide preventive interventions were considered high quality. Of the highquality studies, all evaluated interventions were indicated.…”
Section: Quality and Transferability To The Swedish Contextmentioning
confidence: 99%
See 1 more Smart Citation